On the taxonomic subdivision of the Brown Olive from Africa and Asia through the reinstatement of Olea europaea subsp. africana (Mill.) P.S. Green - (:unkn) unknown (My University, 2024)
The classification of the Olive tree complex (Olea europaea L.) underwent numerous taxonomic changes before a consensus was seemingly reached two decades ago through the combination of morphological, chemical, cytological and molecular evidence that supported the identification of six subspecies in the Old World. While several authors claimed that Brown Olive populations from Africa and Asia were differentiated, there was no attempt to recognize two taxa due to the difficulty to distinguish them based on phenotypic characters and the possibility of a large secondary contact zone between differentiated taxa in NE Africa and the SW Arabian Peninsula. All genetic and phylogenomic studies, however, sufficiently distinguished the Asian Brown Olive, recognized here as Olea europaea L. subsp. cuspidata (Wall. ex G. Don) Cif., from the African Brown Olive, which is here reinstated as Olea europaea L. subsp. africana (Mill.) P.S. Green.
Keywords: African Research